RESULTS OF REVERSING AN ILEOSTOMY WITH AND WITHOUT AN NG TUBE: A CROSS-SECTIONAL STUDY - KHAN , A; IMRAN , A; RAZA , AA; SHAH , SA; GUL , T; ISMAIL , M (Biological and Clinical Sciences Research Journal, 2023)
This study aimed to compare the outcomes of patients who underwent ileostomy reversal surgery with and without a nasogastric (NG) tube. This cross-sectional study was conducted in the surgical department of Mardan Medical Complex in Mardan over one year, from January to August 2023. One hundred patients were recruited randomly, with 75 males (75%) and 25 females (25%). They were divided into two groups: Group 1 received NG tubes, while Group 2 did not. A customized proforma was used to collect information, which was then analyzed using SPSS version 22. The study population comprised 100 females and 75 (65%) males. The mean age of Group 1 was 25.22 years, and that of Group 2 was 26.11 years. The average hospital stay for Group 1 was 05.55 ± 02.45, while that of Group 2 was 04.62 ± 01.66. In Group 1, 7 (07.5%) patients experienced abdominal distension, while 5 (5%) patients in Group 2 experienced the same. Additionally, 62.35% of Group 1 patients passed flatus at a mean time of 47 ± 04.48 hours, while those in Group 2 passed flatus at 35 ± 03.31 hours after ileostomy reversal. The study found that patients who did not receive NG tubes had shorter hospital stays, were less likely to experience abdominal distension, and passed flatus earlier than those who did receive NG tubes. Therefore, it is suggested that NG tubes may not be necessary for all patients undergoing ileostomy reversal surgery.